Perpustakaan dalam Pengembangan Makerspace sebagai Pendukung Metode Pembelajaran Blended Learning di Era Revolusi Industri 4.0 - Ratih Desnita Wilanda; Ninda Hapsari; Marlini Marlini (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2020)
The library has a facility called makerspace which is considered to have a big influence on the blended learning method, especially in the era of the industrial revolution 4.0, developments have been very advanced and flexible thus libraries can easily follow changes in providing services for the user. The research method used in this research is qualitative research with a descriptive analysis method. The results obtained from this study are the perceived influence of makerspace services on blended learning and also the efforts of libraries in makerspace services to the blended learning method.